Boronic acid and nitrofuranyl derivatives as potential therapeutics - Dey, AL (2021)
Chapter 1 commences with a brief panorama of antibacterial development from the very first modern antibacterial agent, namely Salvarsan® to the very last class of clinically significant antibacterials, namely oxazolidinones. It then goes on to briefly outline the practice of modern Drug Design under the heading ‘Medicinal Chemistry & Drug Discovery’, before discussing molecular targets in bacteria and further reiterating that there are several ‘conserved’ molecular targets in bacteria for which there are no antibacterial agents in clinical use as yet, under the heading ‘Current Antibacterial Targets.’